Effect of Specific Lactate Dehydrogenase Antigen from Sheep with Different Prolific Type on Hematology and Antibody Responses of Chicken - Sumaryadi, MY; Prayitno, Prayitno; Manalu, W (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2007)
Maternal serum of thirty nine ewes were used to study hematological and antibody responses of chicken injected with antigen protein of specific LDH obtained from sheep with different littersizes (prolific type). The prolific type of ewes was determined base on littersize (LS), which were low ( 1 â¤Â LS â¤ 1.5), medium ( 1.5 < LS â¤ 2.0), and high (LS > 2.0). There were ten ewes carrying specific LDH protein. The number of animals of low, medium, and high prolific-type ewes was 3, 5, and 2 heads, respectively. The serum was used to produce antigen and injected to chicken to promote antibody production of anti LDH. The results of research showed that different prolific-type has no significant (P>0.05) effects on hematological and antibody titer of chicken.Â However, hematological status of chicken injected with specific LDH antigen was significantly (P<0.05) higher than control. It can be concluded that production of specific protein anti LDH can be done in layer by injection of antigen from ewes. Product of specific protein anti LDH of prolific ewes still needs field test for its accuracy for selection of ewes with different prolific type. (Animal Production 9(1): 40-44 (2007)Â Key Words: hematology, antibody, LDH, ewesÂ